2004
DOI: 10.1111/j.1439-0507.2004.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytes in the rural area of Duzce, Turkey

Abstract: A total of 227 subjects (112 were male and 115 female), who were residents of the rural region of Duzce, were examined for dermatomycosis. A total of 120 samples (47 nail fragments, 73 skin scales) were collected from 81 patients for mycological analysis on the basis of the results of clinical evaluation. All specimens collected were analysed by direct microscopy and culture. Positive results were detected in the cultures of 53 (44.1%) of the 120 samples. About 46 (86.7%) samples also presented positive result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 13 publications
(19 reference statements)
8
36
0
1
Order By: Relevance
“…These results are in agreement with those of earlier investigators, who also reported a higher prevalence of onychomycosis in females than males [19,20]. By contrast; some studies have reported onychomycosis in males more than females [16,21]. Difference in the prevalence of onychomycosis in males and females in the Arabian Gulf may be attributed to the vast difference in lifestyle and propensity to micro-trauma [22].…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with those of earlier investigators, who also reported a higher prevalence of onychomycosis in females than males [19,20]. By contrast; some studies have reported onychomycosis in males more than females [16,21]. Difference in the prevalence of onychomycosis in males and females in the Arabian Gulf may be attributed to the vast difference in lifestyle and propensity to micro-trauma [22].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, M. canis and T. verrucosum has very low frequency (1.0% and 0.3% respectively) and tinea capitis was rare (1.4%). This was in agree with the data reported from Aegean [32] and western Black Sea region of Turkey [33], but higher M. canis frequency was reported from Central Anatolia [29].…”
Section: Resultssupporting
confidence: 82%
“…This was recorded in a randomized study conducted in the rural area of Duzce, Turkey, published in 2004 (no study period available) where tinea pedis (49.1 %) and tinea unguium (35.8 %) were predominant. Furthermore in that study, T. rubrum (62.2 %) was the main aetiological agent, followed by T. mentagrophytes (16.9 %) [54].…”
Section: Middle Eastmentioning
confidence: 97%